Bye bye, GI: The impact of the US military drawdown on local German labor markets - Jan Peter aus dem Moore; Alexandra Spitz-Oener (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
What is the impact of a local negative demand shock on local labor markets? We exploit the unique natural experiment provided by the drawdown of U.S. military forces in West Germany after the end of the Cold War to investigate this question. We find persistent negative effects of the reduction in the U.S. forces on private sector employment, with considerable heterogeneity in terms of age and education groups, and sectors. In addition, the U.S. forces reduction resulted in a rise in local unemployment, whereas migration patterns and wages were not affected.
Keywords: J23; R23; 330; labor demand shock; base closure; employment; wages; Militärstandort; Amerikanisch; Regionale Inzidenz; Regionaler Arbeitsmarkt; Beschäftigungseffekt; Deutschland